(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2015)
The focus of this article is on the concept of “situation”, which lies at the very origin of the Situationist International, as it has been theorized in particular by Guy Debord. The aim of this paper will be to show the relationship between Debord’s concept of situation and the concept of repetition as theorized by Deleuze in Difference and repetition (1968). Such a conceptual proximity allows us to grasp some less known aspects of Debord’s thought, in respect to the critical part of his own reflection, which is much more known. Both authors share a similar conception about the peculiar structure of repetition like its own specific temporality. Such a commonality is manifest in various typical situationist proceedings; in particular: dérive, détournement and cinema (considered as way to overcome the alienation of art).